Microencapsulation of Citrus sinensis peel extract using synthesised guar gum grafted acrylic acid superabsorbent polymer: Studies on sustainable release kinetics and antimicrobial activity - S B Shruthi; G N Rameshaiah
Citrus sinensis peel, a major waste fraction of C. sinensis fruit, contains phytochemicals such as flavonoids, terpenoids, saponins, tannins, etc., which find application in the wide horizon. In order to protect an active component from physical and chemical reactions and retain its functional properties, microencapsulation is a technique that creates a functional barrier between core and shell material. This study tailored shell material to obtain guar gum grafted acrylic acid superabsorbent polymer (GG-g-AASAP) via microwave irradiated graft polymerisation. The effect of monomer (acrylic acid), initiator (Ammonium persulfate), crosslinker (methylene bis acrylamide), and reaction time on grafting percentage was evaluated and optimised. The GG-g-AA SAP was characterised by Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM) to confirm the grafting of acrylic acid onto guar gum. The peel of C. sinensis was extracted using an aqueous extraction method with a yield percentage of 10.8%. Phytochemical qualitative analysis illustrates the presence of various phytochemicals like flavonoids, tannins, saponins, terpenoids, etc.; C. sinensis was encapsulated by coacervation phase separation method using synthesised GG-g-AA SAP, which resulted in the encapsulation efficiency of 76.8%. Release kinetics followed zero-order kinetics and the Korseymeyermodel, which approves super case II transport with sustainable release. Encapsulated C. sinensisis tested against a gram-negative bacteria, Escherichia coli, and a gram-positive bacteria, Bacillus subtilis, which exhibited antibacterial properties. The results depict a higher zone of inhibition for encapsulated C. sinensis than that without encapsulation. The study suggests that encapsulation has increased the antibacterial property of C. sinensis due to barrier protection from GG-g-AA SAP.